Big Five and Dark Triad personality traits as predictors of multicultural attitude and efficacy - Ahmet Kayiş; Mustafa Akcaoğlu (Termedia Sp. z.o.o., 2021)
BackgroundThe advances in communication and transportation facilities have accelerated the formation of multicultural societies worldwide. Personality traits may be one of the most important indicators of adapting to multicultural environments. Educational environ-ments are multicultural in terms of the composition of students they serve. The present study investigated the predictive role of Big Five and Dark Triad personality traits on multicultural attitude and efficacy (MAE) among teacher candidates.Participants and procedureThe study population comprised of teacher candidates (N = 404) studying in Turkey. In order to collect data, Big Five personali-ty and the Dark Triad, the Adjective Based Personality Scale and the Dark Triad Dirty Dozen Scale were used respectively. In addition, data regarding MAE were collected through the Multicultural Efficacy Scale.ResultsThe results showed that openness to new experience positively (β = .16, p < .01) and psychopathy negatively (β = –.16, p < .01) predicted multicultural attitude. On the other hand, multicultural efficacy was positively predicted only by openness to new experience (β = .32, p < .001). Therefore, openness and psychopathic traits can play an important role in explaining multi-cultural attitude and efficacy. Also, there is no significant difference with regard to teacher candidates’ multicultural efficacy and attitudes according to their grade level.ConclusionsIndividuals with openness to new experiences personality trait have a positive attitude towards multiculturalism, and they view themselves as competent to get involved in multicultural environments. On the other hand, individuals with the psychopathy personality trait have negative attitudes towards multiculturalism.
Keywords: dark triad; teacher candidates; big five personality traits; multicultural education; Psychology; Original Article; multiculturalism; BF1-990; 4. Education